Relativistic soliton formation in laser magnetized plasma interactions. (May 2016) - Feng, W; Li, J Q; Kishimoto, Y
Abstract: The laser plasma interactions in the presence of strong magnetic field are studied by employing particle-in-cell simulations. Simulations show that the energy absorption of strong laser pulse is mainly characterized by the electron cyclotron resonance heating (ECRH) when the magnetic field is large enough. However, it is found that for a weaker magnetic field, a standing or moving soliton can be generated in some moderate laser intensity regions, greatly enhancing the laser absorption. The laser intensity for the soliton heating decreases as the magnetic field increases. Furthermore, the soliton position moves towards the front boundary when the laser intensity or magnetic field strength increases.